Implementation of Balanced Scorecard in Corporate Strategic Management - Eva Yuniarti Utami; Rosita Mei Damayanti; Diah Pramesti; Dama Yuninata; Rohmawan Adi Pratama (West Science Journal Economic and Entrepreneurship, 2023)
This study looks into how the Balanced Scorecard (BSC) was implemented in a West Javan manufacturing company and how it affected strategic management and organizational performance. A mixed-methods approach was used, integrating quantitative data obtained from surveys and performance measures with qualitative data from in-depth interviews and document analysis. The qualitative results draw attention to the intricate implementation process, which includes communication tactics, strategic goal-setting, and ongoing modification. Difficulties were noted, including resistance to change and worries about an increase in workload. Positive employee attitudes, greater alignment with company goals, and advancements in financial and operational measures are all indicated by the quantitative outcomes. The study offers insightful information to companies thinking about implementing BSC, highlighting the significance of open communication, staff involvement, and ongoing adaption for success.